Mobile banking: a study on adoption stages using government adoption model and the role of demographic moderators. (21st January 2022) - Gonçalves, Rui; Cabrita, Inês; Pereira, Leandro; Costa, Renato Lopes Da; Dias, Álvaro; Silva, Rui Vinhas Da
The present study's objective was to find the most relevant factors for adoption of mobile banking in Portugal at each service stage, using the GAM model, and to understand the role of demographic moderators. The research contributes to fulfil the gap in the literature of factors affecting mobile banking adoption according to adoption stages, being the first study to address the role of moderators in the described context. It was found that perceived functional benefit is the most relevant predictor at static and transaction stages, and availability of resources is the most relevant in the interaction stage. Regarding demographic moderators, only the relation between perceived awareness and mobile banking at the static stage was significantly moderated by gender.